Sida tuberculata extract reduces the nociceptive response by chemical noxious stimuli in mice: Implications for mechanism of action, relation to chemical composition and molecular docking. (29th October 2018) - da Rosa, Hemerson S.; Coelho, Igor S.; da Silva, Morgana Duarte; Fernandes, Mariana S.; Bertelli, Pablo Ricardo; Minetto, Luciane; Moura, Sidnei; de Paula, Fávero; Santos, Adair R.; Mendez, Andreas S. L.; Folmer, Vanderlei
Abstract : Sida tuberculata R.E.Fr. (Malvaceae) is a medicinal plant widely found in Southern Brazil, and popularly used for inflammatory disorders and to pain relief. A phytochemical analysis followed by an investigation about antinociceptive potential and mechanism of action were performed with leaves and roots extracts. Methanolic extracts, designated as S. tuberculata leaves extract (STLE) and S. tuberculata roots extract, were analyzed both by UHPLC–MS. The in vivo antinociceptive potential of STLE (10–300 mg kg −1 ) was assessed in mice subjected to the acetic acid‐induced abdominal writhes and formalin model. Agonist/antagonist tests and computational docking suggest the involvement of opioid and adenosinergic systems. The main chemical class detected on extracts was the ecdysteroids, and 20‐hydoxyecdysone (20HE) was confirmed as the major phytoconstituent. The pretreatment with STLE (100 mg kg −1 ) reduced more than 70% abdominal contortions induced by acetic acid model and produced significant inhibition on formalin‐induced licking response. The mechanism of action study revealed STLE might act through opioid and adenosine systems. Molecular docking suggested kaempferol derivative and 20HE might interacting with μ‐opioid receptor. Thus, the results suggest the existence of antinociceptive potential from S. tuberculata extracts being in accordance to the traditional use.